2015
DOI: 10.1111/anae.13098
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of ultrasound versus electrical stimulation for peripheral nerve location and blockade

Abstract: SummaryWe systematically reviewed peripheral nerve blockade guided by ultrasound versus electrical stimulation. We included 26 comparisons in 23 randomised controlled trials of 2125 participants. Ultrasound reduced the rate of pain during the procedure, relative risk (95% CI) 0.60 (0.41-0.89), p = 0.01. Ultrasound with or without electrical stimulation reduced the rate of analgesic or anaesthetic rescue versus electrical stimulation alone, relative risk (95% CI) 0.40 (0.29-0.54) and 0.29 (0.16-0.52), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 35 publications
0
36
0
1
Order By: Relevance
“…Systematic reviews and meta-analyses of randomized controlled trials (RCTs) demonstrate that ultrasound-guided techniques improve outcomes (faster block performance, fewer needle passes, reduced incidence of vascular puncture, faster sensory block onset, and success rate) when compared with traditional techniques. [1][2][3][4][5][6] Limitations of existing RCTs comparing ultrasound guidance with traditional techniques included having operators with a wide range of expertise, including both consultant and trainees performing the intervention. The authors of a 2015 review noted that, currently, there are no high-quality randomized studies that evaluate the learning of ultrasound-guided peripheral nerve blockade by novices.…”
Section: Resultsmentioning
confidence: 99%
“…Systematic reviews and meta-analyses of randomized controlled trials (RCTs) demonstrate that ultrasound-guided techniques improve outcomes (faster block performance, fewer needle passes, reduced incidence of vascular puncture, faster sensory block onset, and success rate) when compared with traditional techniques. [1][2][3][4][5][6] Limitations of existing RCTs comparing ultrasound guidance with traditional techniques included having operators with a wide range of expertise, including both consultant and trainees performing the intervention. The authors of a 2015 review noted that, currently, there are no high-quality randomized studies that evaluate the learning of ultrasound-guided peripheral nerve blockade by novices.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Choi and Brull [14] did not find any significant difference between traditional nerve localisation techniques and ultrasound guidance for any outcomes in their meta-analysis. In their recent systematic review, Munirama and McLeod [15] reported no difference in postoperative neurological side effects, though they reported a reduced incidence of analgesic or anaesthetic rescue in the ultrasound group. Other authors have demonstrated comparable onset times and success rates with ultrasound and nerve stimulation guidance in other types of blocks [16].…”
Section: Discussionmentioning
confidence: 98%
“…Ultrasound guided technique had increased the precision for drug injection at the close vicinity of the nerve structure thus minimizing the complications like phrenic nerve palsy and vascular puncture in both the study group. 20 Similarly the rotator cuff surgery, nerve block anesthesia provides superior same day recovery over general anesthesia. Anesthesiology.…”
Section: Discussionmentioning
confidence: 99%